6th International Symposium on Tonal Aspects of Languages (TAL 2018) 2018
DOI: 10.21437/tal.2018-22
|View full text |Cite
|
Sign up to set email alerts
|

Perception and lexical encoding of tone in a restricted tone language: Developmental evidence from Limburgian

Abstract: Within the large family of tone languages, differences exist with respect to the importance and phonetic realization of tones. It remains unclear how these differences influence the acquisition and processing of lexical tone. Limburgian, spoken in the south of the Netherlands, is assumed to have lexical tone, but it has a lower functional load than for example Mandarin Chinese. Moreover, lexical tone in Limburgian is subject to an intriguing amount of surface variation [1]. We compared performance of native Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Nor do they require the introduction of any theoretical apparatus not offered by phonological theory. Research has shown that F0 is the main perceptual correlate in East Limburgish (Fournier et al 2006), as well as in the Mayen and Arzbach dialects (Werth 2011: 145-234), and speakers of the Roermond dialects have been shown to be more sensitive to pitch contrasts than speakers of (non-tonal) standard Dutch (Ramachers et al 2018). Also, the salience of the tone contrast is influenced by the intonational context in the tonal dialect of Roermond, but the quantity contrast in etymologically identical words in the dialect of Weert is not (Heijmans 2003, Fournier et al 2006.…”
Section: The Place Of Franconian Dialects Among Languages With Lexicamentioning
confidence: 99%
“…Nor do they require the introduction of any theoretical apparatus not offered by phonological theory. Research has shown that F0 is the main perceptual correlate in East Limburgish (Fournier et al 2006), as well as in the Mayen and Arzbach dialects (Werth 2011: 145-234), and speakers of the Roermond dialects have been shown to be more sensitive to pitch contrasts than speakers of (non-tonal) standard Dutch (Ramachers et al 2018). Also, the salience of the tone contrast is influenced by the intonational context in the tonal dialect of Roermond, but the quantity contrast in etymologically identical words in the dialect of Weert is not (Heijmans 2003, Fournier et al 2006.…”
Section: The Place Of Franconian Dialects Among Languages With Lexicamentioning
confidence: 99%